Effects of dietary supplementation of Chlorella vulgaris on oxidative stress attenuation and serum biochemical profile of pregnant New Zealand White rabbits - SIKIRU, A B; ARANGASAMY, A; ALEMEDE, I C; EGENA, S S A; IPPALA, J R; BHATTA, R (The Indian Journal of Animal Sciences, 2021)
Oxidative stress negatively affects animals during gestation period and this condition is almost inevitable in the Tropics because of temperature elevation; therefore, objective of this study was evaluation of antioxidant effects of Chlorella vulgaris supplementation in pregnant rabbits. New Zealand white rabbits (40) were randomly distributed into five groups (n = 8) on day 0 of their gestation and were supplemented with 0, 200, 300, 400 and 500 mg Chlorella vulgaris biomass per kg body weight respectively throughout the gestation period. Blood was collected from the animals in the last week of gestation for serum oxidative stress and biochemical profile assessments. There was significant difference in serum malondialdehyde concentration, total antioxidant capacity but protein carbonyl content was not significantly different. There was also significant difference in superoxide dismutase activity, catalase activity and glutathione concentration. Furthermore, the results showed that serum biochemical profiles of the rabbits were within the normal ranges for healthy rabbits. The study therefore concluded that supplementation of Chlorella vulgaris significantly protects the rabbits against oxidative stress damage and has no deleterious effects on their organs function; hence, the microalga was recommended as an antioxidant supplement for pregnant rabbits.